Sistem Pemantauan Suhu dan Nutrisi Tanaman Pakcoy pada Hidroponik Menggunakan Metode Logika Fuzzy - Jessica Desi Imelda (Modem : Jurnal Informatika dan Sains Teknologi., 2025)
Technological developments in the agricultural sector, especially in the hydroponic method, provide solutions for optimizing plant growth in urban environments. This research integrates ESP32 microcontroller technology with a DS18B20 temperature sensor and TDS sensor to monitor and control temperature and nutrient quality in a hydroponic system. In addition, the Sugeno fuzzy logic method is used for automatic water quality monitoring.